PERANCANGAN VIDEO LIRIK BAND DISTRICT HARDCORE MELALUI MEDIA AUDIO VISUAL - Fadhil Mutawakkil; hendra afriwan (Universitas Negeri Padang, 2020)
District is one of Hardcore band that have a Melodic Hardcore style from Bukittinggi city. District are the pioneer of Melodic Hardcore genre in Bukittinggi city, made this genre as their characteristic that brought by District. Lyrics from District is containing massage about rebellion and resistance to oppressions. Yet the messages from the lyrics is less delivered, because of the audience have a problem to understand the lyrics.The design of this lyric video is expected can be an effective communication media to delivered contain and message from District song lyrics and suit with low budget also style of Hardcore music.This lyric video will be showing Let’s Revolt lyric from District. Besides showing the lyrics, Motion Graphics will be shown to illustrating to give some better impressions for this lyric video. This lyric video will have theme of war, mass demonstration, and justice.Keyword : indie band, hardcore, Let’s Revolt, District, Lyric Video